PERBANDINGAN EFEKTIFITAS RENDAM KAKI AIR HANGAT DAN AROMATERAPI MAWAR TERHADAP KUALITAS TIDUR LANSIA DI BALAI SOSIAL LANJUT USIA MANDALIKA NTB - Ageng Abdi Putra (Jurnal PRIMA, 2017)
Sleeping is a basic need of human being that should be fulfilled. Sleeping disorder may cause serious problem or even the decrease of life quality. This is often faced by elderly which cause the decrease of sleep quality. The therapy of foot soaking in warm water and the rose aromatherapy are non-pharmacological therapy that is useful to overcome the sleep problem. This research is aimed at determining the effectiveness comparison between foot soaking in warm water and rose aromatherapy on the sleeping quality of elderly in Mandalika Social House for Elderly West Nusa tenggara. This research was designed to be quasi-experimental study (two-group comparison pretest and post test design). The samples were 22 respondents selected through purposive sampling. The instrument to measure the sleep quality is Pittsburgh Sleep Quality Index. The data were analyzed with mann Whitney U. Based on the statistic test with the value of significance is 0.136 > 0.05 showing that Ha is rejected and H0 is accepted which means that there is difference between foot soaking in warm water and rose aromatherapy on the sleeping quality of elderly. The research inferred that there is the effectiveness between foot soaking in warm water and rose aromatherapy on the sleeping quality of elderly. So that both foot soaking in warm water and rose aromatherapy could be considered as alternative treatment to help elderly from sleep disorder of elderly. Keywords : sleeping need, elderly, relaxation deep breathing